1999
DOI: 10.1038/sj.jea.7500064
|View full text |Cite
|
Sign up to set email alerts
|

Missing annual external radiation dosimetry data among Hanford workers

Abstract: Epidemiological studies of workers employed at the Hanford Site have been underway for nearly 30 years. Although the external radiation dosimetry program at Hanford has been fairly comprehensive, some workers included in previous epidemiological analyses have periods of employment during which there are missing annual external radiation dosimetry records. In this report, employment history records and annual external dosimetry records have been used to investigate the extent of missing annual external dosimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…The percentage of missing annual external dosimetry records among male SRS workers (4%) is comparable to the 6% missing annual external dosimetry records among male Hanford workers (Richardson et al, 1999) and the 5% missing annual dose records reported among white males employed at ORNL (Wing et al, 1991). Also similar to previous findings from evaluations of the dosimetry programs at ORNL and Hanford, we found that coverage was more complete in later historical periods than in earlier years of operation.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The percentage of missing annual external dosimetry records among male SRS workers (4%) is comparable to the 6% missing annual external dosimetry records among male Hanford workers (Richardson et al, 1999) and the 5% missing annual dose records reported among white males employed at ORNL (Wing et al, 1991). Also similar to previous findings from evaluations of the dosimetry programs at ORNL and Hanford, we found that coverage was more complete in later historical periods than in earlier years of operation.…”
Section: Discussionsupporting
confidence: 78%
“…So, the nearby estimation procedure tends to lead to a small overestimate of the value for an unmonitored dose year in which the true dose was zero and a small underestimate of the value for an unmonitored year in which the true dose was greater than zero. These findings are similar to patterns reported in a previous application of the nearby procedure to data for workers from the Hanford Site (Richardson et al, 1999). If we had information that indicated that a clerical worker was employed in an area in which the dose rate was zero then we could assign a zero dose to that year.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…21 Although annual dose records were available for most production workers in most years, a substantial proportion of missing values occurred in earlier time periods, especially for clerical workers and women. 20 Missing values were estimated by a 13 step algorithm that relied on each worker's dose in neighbouring years, and, if not available, on the mean dose for workers of the same occupation and sex in the same year. 20 Statistical analysis An SAS computer program 22 was used to tabulate persondays and deaths in categories defined by the crossclassification of cumulative radiation dose and covariates of interest: age-at-risk, birth cohort, race, sex, socioeconomic status (SES), employment status, in vivo monitoring, and plutonium exposure potential.…”
Section: Methodsmentioning
confidence: 99%
“…The primary occupational exposure under investigation at Hanford has been external penetrating ionizing radiation. These external exposures have been routinely quantified using personal dosimeters for a majority of workers included in epidemiologic studies [Gilbert, 1990;Kneale et al, 1991;Gilbert and Fix, 1996;Richardson et al, 1999Richardson et al, , 2000. Epidemiologic studies have demonstrated dose-response relationships for cancer mortality and external radiation exposures at older ages [Stewart and Kneale, 1989Stewart, 1993, 1995], but not for cumulative exposures across all ages [Gilbert et al, 1989[Gilbert et al, , 1993a.…”
Section: Introductionmentioning
confidence: 99%